Taming Solvent–Solute Interaction Accelerates Interfacial Kinetics in Low‐Temperature Lithium‐Metal Batteries - Jin, Cheng‐Bin; Yao, Nan; Xiao, Ye; Xie, Jin; Li, Zeheng; Chen, Xiang; Li, Bo‐Quan; Zhang, Xue‐Qiang; Huang, Jia‐Qi; Zhang, Qiang (Advanced materials (Weinheim), 2023)
Lithium (Li)‐metal batteries promise energy density beyond 400 Wh kg−1, while their practical operation at an extreme temperature below −30 °C suffers severe capacity deterioration. Such battery failure highly relates to the remarkably increased kinetic barrier of interfacial processes, including interfacial desolvation, ion transportation, and charge transfer. In this work, the interfacial kinetics in three prototypical electrolytes are quantitatively probed by three‐electrode electrochemical techniques and molecular dynamics simulations. Desolvation as the limiting step of interfacial processes is validated to dominate the cell impedance and capacity at low temperature. 1,3‐Dioxolane‐based electrolyte with tamed solvent–solute interaction facilitates fast desolvation, enabling the practical Li|LiNi0.5Co0.2Mn0.3O2 cells at −40 °C to retain 66% of room‐temperature capacity and withstand remarkably fast charging rate (0.3 C). The barrier of desolvation dictated by solvent–solute interaction environments is quantitatively uncovered. Regulating the solvent–solute interaction by low‐affinity solvents emerges as a promising solution to low‐temperature batteries. Desolvation is validated as the predominant contributor to energy loss at low temperatures, largely overwhelming the contributions from other interfacial ion transportation processes. A rational and original design by taming solvent–solute interaction with low‐affinity solvents like 1,3‐dioxolane is proposed to enable high capacity and durable operation of practical lithium‐metal batteries at −40 °C.